PERKEMBANGAN NILAI-NILAI KERUKUNAN ANTAR UMMAT BERAGAMA PADA MASYARAKAT MAJEMUK - Fibriana, Rosania Mega (2014)
This thesis presents the results of the study of the development of the values of inter-religious harmony in the society of Kalibago Village. The focus in this study were how the development of the values of inter-religious harmony was and how the people of Kalibago Village built the inter-religious harmony in their society? The grand theory employed to discuss the focus is religious pluralism by Hick. The research questions were: what process the people of Kalibago Village do in order to create inter-religious harmony? What factors unify the people of Kalibago Village? How is the realization of values of the inter-religious harmony in the society of Kalibago Village? In order to answer these questions, the data about how a plural society was formed and factors unifying the society of Kalibago Village as well as contributing into inter-religious harmony in Village were obtained. These data were obtained by using direct observation in Kalibago Village and in-depth interviews with the people of Kalibago Village, which were also supported by demographic data analysis of Kalibago Village. The data were analyzed by using data analysis techniques suggested by Miles and Huberman. The results of the study were as follows: 1) the process in building inter-religious harmony in Kalibago Village started by the formulation of plural society through the transfer of religion done by some people. The transfer of religion created inter-religious conflict impacting their daily lives. However, this conflict could be solved by the colloquy, which resulted in the development of mutual agreement. In supporting the development of inter-religious harmony, the society regularly holds annual celebrations, which are resik deso and 17 August party. 2) the factors unifying the society of Kalibago Village are that the society upholds a kinship relationship among people of Kalibago Village, maintains a mutual peace, and prioritizes the humanity in supporting their social life. 3) the realization of values of inter-religious harmony has been in the process since 1965 up until now. The values of inter-religious harmony are manifested in being respect, appreciative, tolerant, mutually cooperative, and open-minded. The manifestation of being tolerant among inter-religious society in Kalibago Village created traditions by sending cake and visiting that are done in the religious holidays.